SUBCUTANEOUS EMPHYSEMA OF CHEST WITHOUT BONY INJURY BY BLUNT FORCE – REPORT OF TWO CASES (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
of two cases, both presenting as subcutaneous emphysema of chest without pneumothorax or any bony injury to chest by blunt non-penetrating objects. In one case an allegation was made by accused a syringe has introduced that air. To confirm the allegation air was introduced with a 50 cc syringe in dead bodies subcutaneously in chest & emphysema could be produced easily.  In second case there was extensive surgical emphysema without pneumothorax or any bony injury to chest. It can be concluded that subcutaneous emphysema can occur without bony injury to chest, as well as it can be produced artificially but it requires further confirmation by experiments on living.
Keywords: Subcutaneous Emphysema; Trauma